2014
DOI: 10.1016/j.quageo.2013.01.008
|View full text |Cite
|
Sign up to set email alerts
|

The geology and geochronology of Al Wahbah maar crater, Harrat Kishb, Saudi Arabia

Abstract: Al Wahbah is a large (~2.2 km diameter, ~250 m deep) maar crater in the Harrat Kishb volcanic field in western Saudi Arabia. It cuts Proterozoic basement rocks and two Quaternary basanite lava flows, and is rimmed with an eroded tuff ring of debris from the phreatomagmatic explosion that generated the crater. A scoria cone on the northern wall of the crater was dissected by the explosion and exposes a dolerite plug that was intruded immediately prior to crater formation. The dolerite plug yields a 40 Ar/ 39 Ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Along the crater wall localized lava spatter deposits overly lava flows, indicating that prior to crater formation Hawaiian lava fountaining occurred along the vents that likely followed a fissure alignment of roughly NW-SE. Recently obtained Ar/Ar geochronology has also confirmed that the pre-maar scoria cone (1.147 +/-0.004 Ma) is slightly younger than the underlying lava flow sheets (1.261 +/-0.021 Ma -1,178 +/-0.007 Ma) [38]. This new geochronology gives the formation of Al Wahbah maar the minimum age of 1.147 +/-0.004 Ma and clearly separates it from the uppermost pre-maar lava flow emplacement period [38].…”
Section: Al Wahbah Crater Geotopementioning
confidence: 74%
See 1 more Smart Citation
“…Along the crater wall localized lava spatter deposits overly lava flows, indicating that prior to crater formation Hawaiian lava fountaining occurred along the vents that likely followed a fissure alignment of roughly NW-SE. Recently obtained Ar/Ar geochronology has also confirmed that the pre-maar scoria cone (1.147 +/-0.004 Ma) is slightly younger than the underlying lava flow sheets (1.261 +/-0.021 Ma -1,178 +/-0.007 Ma) [38]. This new geochronology gives the formation of Al Wahbah maar the minimum age of 1.147 +/-0.004 Ma and clearly separates it from the uppermost pre-maar lava flow emplacement period [38].…”
Section: Al Wahbah Crater Geotopementioning
confidence: 74%
“…Recently obtained Ar/Ar geochronology has also confirmed that the pre-maar scoria cone (1.147 +/-0.004 Ma) is slightly younger than the underlying lava flow sheets (1.261 +/-0.021 Ma -1,178 +/-0.007 Ma) [38]. This new geochronology gives the formation of Al Wahbah maar the minimum age of 1.147 +/-0.004 Ma and clearly separates it from the uppermost pre-maar lava flow emplacement period [38]. While the chronological order of events seems to be correct, the geological evidence demonstrates that the uppermost part of the pre-maar lava flow units is in close genetic relationship with the pre-maar scoria cone.…”
Section: Al Wahbah Crater Geotopementioning
confidence: 74%
“…Although this unique geotope resulted in different geological components in terms of time and age, the age of the crater is still not known. However, as per the calculation of age using the yield 40 Ar/ 39 Ar, dolerite plug of 1.147 ± 0.004 Ma, lower basalt flows, 1.261 ± 0.021 Ma and upper basalt flows 1.178 ± 0.007 Ma (AbdelWahab et al 2014). But age of 1.147 ± 0.004 Ma is the best estimation time of Al Wahbah crater formed.…”
Section: Site Descriptionmentioning
confidence: 98%
“…Al Wahbah Mountain is 1105 m above sea level. Very few geological studies on Al Wahbah crater have been conducted (Grainger 1996;Moufti et al 2013;AbdelWahab et al 2014); however, all of them agreed that the crater was formed by explosive eruptions or volcanic explosions as a result of the interaction between magma and groundwater. Continuous volcanic eruptions resulted in phreatic activities that led to deposition of rocks, lava and debris around the crater and created multiple lava flows, the tuff ring, tephra ring, basement, dolerite plug, scoria cones and wall.…”
Section: Site Descriptionmentioning
confidence: 99%
See 1 more Smart Citation